Gender Equality at the Agriculture Office in Kabupaten Enrekang - Suparman Suparman (Edumaspul: Jurnal Pendidikan, 2019)
Gender Equality in Enrekang District (Case Study of Agricultural Service Personnel). This study aims to determine how people's perceptions of gender equality in the Agriculture Office of Enrekang District; and to find out the extent of gender equality in the Agriculture Office of Enrekang District. This type of research is a descriptive qualitative method; data collection is used by observation, in-depth interviews, documentation techniques from the results of photographs and archives owned by the local government. In this study, the target of the study was the first employee of the Agriculture Office of Enrekang District, the second community considered to be able to provide information or data in accordance with the research. The results of this study indicate that gender equality in public services, especially the Agriculture Office of Enrekang District, has not yet become a reality. This is evidenced that the number of employees with a ratio of the number of men is 89 (66%) people and the number of women is 45 (34%) people. The results of interviews with the community showed that support for gender equality, women's freedom to express opinions and work outside, especially working at the Agriculture Office in Enrekang District. The implication of the study were expected to provide knowledge about gender equality in the profession and provided understanding to the public about the role of women in the community.